Analisis Strategi Pelayanan dan Transparansi Bagi Hasil dalam Meningkatkan Minat Menabung Nasabah (Studi Kasus BMT NU Cabang Pragaan) - Hidayati, Nurul; Apriliana, Apriliana (Multiverse: Open Multidisciplinary Journal, 2023)
Islamic banks operate based on Islamic principles, which involve collecting and distributing funds without charging interest but through profit-sharing agreements. This study adopts a qualitative approach to provide descriptive narratives on observed issues. Data collection involves primary and secondary sources, utilizing methods such as observation, interviews, and documentation. Data analysis involves systematic organization and interpretation of observations and interviews to enhance the researcher's understanding and present findings to others. BMT NU Pragaan Branch employs a service strategy to enhance customer interest in saving, such as the savings shuttle service. Opening a savings account requires minimal documentation, including photocopies of identification cards, family cards, a passport-sized photo, and a contact number. Profit sharing at BMT NU Pragaan Branch depends on the agreed timeframe and the amount saved, adhering to mutually agreed terms between the bank and members.